METHODS OF WORKING ON THE TEXT IN UZBEK LANGUAGE LESSONS - Raximjanov Masrur Nugmanovich (Galaxy International Interdisciplinary Research Journal, 2021)
The highest form of creative-practical work is the creation of text. Because the text shows students’ knowledge of linguistic phenomena, creative thinking, accurate and fluent expression of the product of thought in oral and written forms, using the rich potential of the Uzbek literary language. So learn text language.